JENIS-JENIS BINTANG LAUT, BULU BABI, DAN TERIPANG (ECHINODERMATA) DI PERAIRAN PULAU TUNDA KABUPATEN SERANG - Agung Setyo Sasongko; Daniel Julianto Tarigan; Ferry Dwi Cahyadi; Lio Yonanto; Muhammad Nur Salim; Aang Fuad Hasan; Hana Azalia (Fakultas Perikanan dan Ilmu Kelautan, 2020)
Echinoderms are fundamentally good indicators of health and status of coralline communities in marine waters. Substrat of sandy, rububle, and coral reefs are good habitat for Asteroidea, Echinoidea, and Holothuroidea. This study aims to identify sea star (Asteroidea), sea urchin (Echinoidea), and sea cucumber (Holothuroidea) species from Tunda Island waters of Serang. Asteroidea and Echinoidea observed using the line transect method used, through subjects observation within the same distance between the transect and the transect square with observations of 2.5 m on the right and left of line transect. Observations of the habitat covered substrate and depth, while the total number of sea stars, sea urchins, and sea cucumbers at each station were recorded, which were then documented and identified based on their morphological characteristics. The waters on Tunda Island found 2 species of the Asteroidea class, namely Linckia laevigata and Culcita novaeguneae, 3 species of Echinoidea Diadema antilarum, Diadema setosum, Echinomerta mathaei, and 3 species of Holothuroidea Holothuria atra, Holothuria leucospilota, Bohadschia graeffei.